Endo-pectinase Production by Bacillus pumilus NRRL B-212 and Optimization by RSM using Sugar Beet Pulp - Tepe, Ozlem; Dursun, Arzu Y. (Croatian Soc Chemical Engineering Technology, 2021)
The present study aimed at optimization of culture conditions for endo-pectinase production by Bacillus pumilus NRRL B-212. In the first stage of the study, submerged fermentation experiments were performed to investigate effects of initial pH, carbon and nitrogen sources, salts and phosphate on endo-pectinase activity and maximum enzyme production was at pH: 8. The effect of initial pectin concentration on enzyme production was examined, and 1 % (w/v) pectin concentration was selected as the optimum pectin concentration. Yeast extract, (NH4)(2)SO4, and peptone were used as nitrogen sources, and the medium containing 0.05 % (w/v) ammonium sulphate was the medium where maximum activity was achieved. In the experiments investigating the effect of salts, the maximum activity value was determined in the medium containing 0.02 % NaCl. In addition, the effect of phosphate concentration on enzyme production was investigated, and the highest endo-pectinase activity was determined in medium containing 0.3 % K2HPO4 + 0.15 % KH2 PO4. In the second stage of the study, solid-state fermentation studies were performed, and sugar beet pulp was used as agricultural waste. In order to obtain maximum endo-pectinase production and reveal the parameters influencing enzyme activity using sugar beet pulp, a Central Composite Design (CCD) was applied. The highest endo-pectinase activity was obtained as 147.75 U mL(-1) in medium containing 6.78 % sugar beet pulp, 0.48 % (NH4)(2)SO4 and 0.12 % yeast extract.
Keywords: Bacillus pumilus NRRL B-212; endo-pectinase; enzyme production; response surface methodology; submerged fermentation; sugar beet pulp